2023
DOI: 10.1590/1519-6984.275046
|View full text |Cite
|
Sign up to set email alerts
|

Calcium pyruvate in the attenuation of the water deficit on the agro-industrial quality of ratoon sugarcane

M. S. Dias,
F. A. Silva,
P. D. Fernandes
et al.

Abstract: Sugarcane is one of the largest agricultural commodities when considering the export volume and the number of jobs generated. Sugarcane production in the Brazilian Northeast region is generally low due to several factors, including the irregular rainfall distribution, which highlights the importance of studies aimed at mitigating the deleterious effects of water stress. In this scenario, this study aimed to evaluate calcium pyruvate as a water deficit attenuator on the agro-industrial quality of sugarcane in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition to these studies, Dias et al [38] found that the effects of water deficit on the tillering and stalk elongation phases in sugarcane are alleviated by the exogenous application of 30 mM calcium pyruvate.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these studies, Dias et al [38] found that the effects of water deficit on the tillering and stalk elongation phases in sugarcane are alleviated by the exogenous application of 30 mM calcium pyruvate.…”
Section: Resultsmentioning
confidence: 99%